COVID-19 Study: A New Principle Discovery - Lu, Da-Yong; Lu, Ting-Ren (Current Drug Therapy, 2025)
The impact and burden of coronavirus outbreak (COVID-19, SARS-CoV-2) still exists worldwide. Different knowledge, opinions, and techniques determine the various outcomes and potency of preventive and therapeutic strategies. COVID-19 infections, long COVID, and the complexity of treatment variability are challenging issues for therapeutic promotion and cost-effective consideration. To speed up global efforts against COVID-19, clinical diagnosis, therapeutic selections, and drug combination studies should be optimized in different ways. The epidemic condition, vaccination, techniques, and therapeutic options are open to new expeditions. To target infectious and therapeutic variability, biomedical mechanisms and pathways should be understood. Facilitating and enhancing new global machinery and roadmap against viral-induced social damages and potential epidemics should be established for biological and pharmaceutical purposes. Thus, in this study, the ways of medical translation for COVID-19 treatment are discussed.
Keywords: COVID-19